The Effect of Actionbound Application on Academic Success and Attitude on 6th Grade Field Measurement - Korkmaz, Ebru (Tamer KUTLUCA, 2023)
This study aims to examine the effects of activities prepared using the Actionbound application on students' academic achievement and mathematical attitude in the field measurement subject in the 6th-grade mathematics course. The study was designed using a quasi-experimental design with a control group from quantitative research methods. The study group of research consists of students studying in two different 6th grades of a secondary school in the central district of Elazığ province in the school year 2022-2023. The achievement averages of the branches in the previous semester were used in forming the experimental and control groups and in ensuring the equivalence of the branches. The research, which was conducted in parallel with the MoNE curriculum, was applied simultaneously to the experimental and control groups. The research, which used parametric testing procedures due to the normal distribution of the data, was analyzed using the SPSS package program. The results show that the digital learning game developed using Actionbound improves performance and attitude, but does not cause a significant difference between the groups. It is recommended to extend the application period of the study and continue the study for one semester.

This study aims to examine the effects of activities prepared using the Actionbound application on students' academic achievement and mathematical attitude in the field measurement subject in the 6th-grade mathematics course. The study was designed using a quasi-experimental design with a control group from quantitative research methods. The study group of research consists of students studying in two different 6th grades of a secondary school in the central district of Elazığ province in the school year 2022-2023. The achievement averages of the branches in the previous semester were used in forming the experimental and control groups and in ensuring the equivalence of the branches. The research, which was conducted in parallel with the MoNE curriculum, was applied simultaneously to the experimental and control groups. The research, which used parametric testing procedures due to the normal distribution of the data, was analyzed using the SPSS package program. The results show that the digital learning game developed using Actionbound improves performance and attitude, but does not cause a significant difference between the groups. It is recommended to extend the application period of the study and continue the study for one semester.
The Effect of Actionbound Application on Academic Success and Attitude on 6th Grade Field Measurement
Keywords: Mathematics Education; Matematik Eğitimi